1996
DOI: 10.1113/jphysiol.1996.sp021428
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ responses to ATP via purinoceptors in the early embryonic chick retina.

Abstract: 1. The action of adenosine triphosphate on cytoplasmic Ca2P concentration ([Ca2+]1) was studied in the retinal cell of early embryonic chicks with fura-2 fluorescence measurements. The fluorescence was measured from the whole neural retina dissected from chick embryos at embryonic day three (E3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 38 publications
1
42
0
1
Order By: Relevance
“…Purinergic signaling, mainly mediated by ATP, has been speculated to regulate adult neurogenesis because it is important for the proliferation of various cell types during development (Zimmerman, 2006), including cortical radial glial cells (Weissman et al, 2004), retinal progenitors (Sugioka et al, 1996;Pearson et al, 2002;Nunes et al, 2007), and olfactory epithelium progenitors (Hassenklöver et al, 2009) in the CNS. Purinergic signaling receptors and nucleotide breakdown enzymes such as ectonucleoside triphosphate diphosphohydrolase 2 (NTPDase2) and tissue-nonspecific alkaline phosphatase are also present in the SVZ (Braun et al, 2003;Langer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Purinergic signaling, mainly mediated by ATP, has been speculated to regulate adult neurogenesis because it is important for the proliferation of various cell types during development (Zimmerman, 2006), including cortical radial glial cells (Weissman et al, 2004), retinal progenitors (Sugioka et al, 1996;Pearson et al, 2002;Nunes et al, 2007), and olfactory epithelium progenitors (Hassenklöver et al, 2009) in the CNS. Purinergic signaling receptors and nucleotide breakdown enzymes such as ectonucleoside triphosphate diphosphohydrolase 2 (NTPDase2) and tissue-nonspecific alkaline phosphatase are also present in the SVZ (Braun et al, 2003;Langer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Suramin blocked the wave, but pyridoxalphosphate-6-azophenyl-2 0 ,4 0 -disulphonic acid (PPADS) did not have a consistent antagonist action. A study of embryonic chick neural retina [151] (Fig. 8) has shown that the ATP-induced rise in intercellular Ca 2?…”
Section: Retinamentioning
confidence: 99%
“…This suggests that endogenous noradrenaline, acting via ␣-adrenergic receptors, is part of the mechanism controlling neuronal differentiation in the central nervous system. Very little is known about the roles of extracellular ATP in early embryonic development, but this molecule has been shown to cause an increase in intracellular Ca 2ϩ (Ca 2ϩ i ) 2 concentration in a number of embryonic cell types, including dissociated cells from early chick embryos (18), early embryonic chick otocyst (19) and retina (20), cultured astrocytes from embryonic rat spinal cord (21), cultured neurons from embryonic rat brain (22), myotubes cultured from embryonic chick (23), and a murine myoblast cell line (24). Increases in Ca 2ϩ i are known to regulate cell proliferation, migration, and differentiation (15,25), all important processes during embryonic development.…”
mentioning
confidence: 99%
“…Increases in Ca 2ϩ i are known to regulate cell proliferation, migration, and differentiation (15,25), all important processes during embryonic development. The P2 receptor(s) responsible for most of these ATP-activated developmental signals have not been identified, and none have been cloned, although the response of embryonic chick retina is thought to be mediated by a P2Y receptor responsive to UTP (20).…”
mentioning
confidence: 99%